Discrimination and the Private Law in Canada: Reflections on Spence v. BMO Trust Co. - Thomson, Jane (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2019)
Discrimination has long been identified as detrimental to the basic functioning of multicultural countries like Canada. While governments have adopted constitutional law and passed human rights legislation to combat and control discrimination, these laws are inapplicable to a significant portion of Canadian law. Areas of private law, such as wills and trusts are therefore more vulnerable to use by individuals seeking to perpetuate discrimination.The main way that courts in Canada have dealt with this issue is through the use of the doctrine of public policy. As early as the 19th century, private law provisions viewed as restraining another’s freedom of religion or perpetuating discrimination on grounds such as race, ethnicity, or sexual orientation have been found contrary to public policy by Canadian courts and voided accordingly.While the uniquely Canadian jurisprudence in this area continues to evolve, until quite recently, its trajectory appeared to be one of expansion. However, the latest appellate level decision in this area,Spence v. BMO Trust Co., appears to have changed the course of this jurisprudence.  In Spence, the Ontario Court of Appeal found that certain testamentary clauses, no matter how discriminatory in nature, can never be subject to a public policy review. This article argues that while the result of Spence was likely correct on its particular facts, the reasoning of that decision goes too far in its attempt to limit the doctrine’s applicability with respect to discrimination in the private law. Parts of the decision in Spence ignore the key message of past decisions in this area concerning the danger of uncensored discrimination in Canadian society. While reasonable people may disagree on the outcome of any given public policy inquiry, a point that should attract consensus is that the private law should never be an unexamined and impenetrable shelter for discrimination. However, Spence effectively creates an area of the private law immune to legal scrutiny by precluding the use of the common law doctrine that has been used to directly confront and censure discrimination in Canadian private law.